Integrated and Iterative Systems Engineering and Software Requirements Engineering for Technical Systems (Précis) - Holtmann, Jörg; Bernijazov, Ruslan; Meyer, Matthias; Schmelter, David; Tschirner, Christian (Proceedings of the Software Engineering 2017, Lecture Notes in Informatics (LNI), Band P-267)
The development of software-intensive technical systems (e.g., within the automotive industry) involves several engineering disciplines like mechanical, electrical, control, and particularly software engineering. Model-based Systems Engineering (MBSE) coordinates these disciplines throughout the development by means of a discipline-spanning system model. An integral part of MBSE is the requirements engineering on the system level. However, these requirements need to be refined for the discipline-specific development to start, for example, into specific requirements for the embedded software. Since existing MBSE approaches lack support for this refinement step, we conceived a systematic and iterative transition from MBSE to model-based software requirements engineering, which we present in this talk. We automated the steps of the transition where possible, in order to avoid error-prone and time-consuming manual tasks. We illustrate the approach and perform a case study with an example of an automotive embedded system.